EEG coherence in a mental arithmetic task performance in first episode schizophrenia and schizoaffective disorder - Zaytseva, Yuliya; Garakh, Zhanna; Novototsky-Vlasov, Vladimir; Gurovich, Isaac Ya; Shmukler, Alexander; Papaefstathiou, Anna; Horáček, Jiří; Španiel, Filip; Strelets, Valeria B (Clinical neurophysiology, 2018)
OBJECTIVES: To evaluate the coherence values of the cortical bands in patients with first episode schizophrenia and schizoaffective disorder during the performance of a mental arithmetic task. METHOD: We analysed EEG coherence in the resting state and subsequently while counting down from 200 in steps of 7 in 32 first episode schizophrenia patients (SZ), 32 patients with first episode schizoaffective disorder (SA) and 40 healthy controls (HC). RESULTS: Task performance in HC is characterised by decreased coherence in the alpha bands and increased coherence in the beta 2 and gamma bands in frontal sites. In SZ, coherence decreases in the alpha band, whereas in SA it substantially increases in the alpha, beta1, beta 2 and gamma bands. CONCLUSIONS: Despite no differences in performance on a behavioural level, SA patients demonstrate a paradoxical increase in both low and fast frequency bands during the performance of a mental arithmetic task, while, patients with SZ show a decreased coherence in the alpha band, presumably alluding to the excessive excitatory (in SA) and inhibitory (in SZ) mechanisms in cognitive processing. SIGNIFICANCE: The current study provides evidence for the distinction of neurophysiological mechanisms of cognitive processing between SZ and SA.
Keywords: inteligenční testy; Cognition; Schizophrenia; schizofrenie; lidé; kognice; matematika; mužské pohlaví; Female; Intelligence Tests; Adult; Brain Waves; Psychotic Disorders; Mathematics; Male; mozkové vlny; ženské pohlaví; dospělí; Humans; mladiství; psychotické poruchy; Adolescent